Implementasi Kendali Tuning Proportional Integral Derivative (PID) Pada Magnetic Levitation Ball Hybrid Fuzzy-Takagi Sugeno - Giyantara, Andhika; Erdi Astama, Dikanuari; Wicaksono, Himawan (SPECTA Journal of Technology, 2023)
The application of magnetic levitation that is currently developing is on land transportation in the form of maglev trains.Magnetic levitation is a system that uses an electromagnetic field to work against the force of gravity. The common point in application the magnetic levitation is used is the lack of contact and thus no friction this increases efficiency and system life. Magnetic levitation technology is still developing today. The magnetic levitation ball requires a good control method to maintain the ball's position on the mat against the earth's surface. This research implements Hybrid Proportional Integral Derivative (PID) control with fuzzy as a control system on magnetic levitation ball. The research for magnetic levitation ball uses Auto Tuning PID and Fuzzy–Takagi Sugeno controls. In the PID system, an auto-tuning system is carried out on simulink MATLAB R2019, and in fuzzy the function is designed to store input in the form of error (e) and delta error (de) while the function displays output in the form of effective height distance. Then defuzzification on fuzzy uses the Center of Area (COA) method. In magnetic levitation research, objects can experience ideal service conditions at a distance of 0.006 m from the end of the solenoid. in the transfer function test to reach a steady state, the risetime is 0.007817 s, the overshoot is 157.051%. then the PID tuning test to reach a steady state obtained a risetime of 0.214371 s, an overshoot of 0.460%. and in the fuzzy-PID hybrid test to reach steady state, the risetime is 0.044902 s and the overshoot is -0.357%.